Analisis Kompetensi Literasi Digital Dan Literasi Baca Guna Menyiapkan Calon Guru Cakap Teknologi Informasi Dan Komunikasi - Ai Siti Nuratilah; Alfira Putri Febryanis; Neng Riski Ayu Utami; Rania Roka; Sofi Kamilatus Sa’diah; Neneng Sri Wulan; Sofyan Iskandar; Nuur Wachid Abdul Majid (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
It should be noted that teachers in this era are required to have skills in conducting learning which can support the achievement of student competencies in this 21st century learning. In the 21st century, participants must understand the rapid development of technology and knowledge. This needs to be addressed by the teacher in order to facilitate students in using technological developments and getting various kinds of learning-based resources Technology. The purpose of this study is to determine the competency of digital literacy and reading literacy prospective teachers have as a form of their own skills to become qualified teachers in this era revolution 4.0. This study used a descriptive qualitative method. Population that being the object of research are students of the Indonesian University of Education Campus in Purwakarta. Determination of the sample using a proportional random technique is done by using a purposive sampling method, namely distributing questionnaires online in google form via social media. After doing research the writer can conclude that Information and Communication technology is very important in learning digital literacy skills and reading literacy. This is so that prospective teachers achieve better results in the learning process.